Changes in Muscle Stress and Sarcomere Adaptation in Mice Following Ischemic Stroke - Tsai, Liang-Ching; Wu, Yi-Ning; Liu, Shu Q.; Zhang, Li-Qun (Frontiers in Physiology, 2020)
While abnormal muscle tone has been observed in people with stroke, how these changes in muscle tension affect sarcomere morphology remains unclear. The purpose of this study was to examine time-course changes in passive muscle fiber tension and sarcomeric adaptation to these changes post-ischemic stroke in a mouse model by using a novel in-vivo force microscope. Twenty-one mice were evenly divided into three groups based on the time point of testing: 3 days (D3), 10 days (D10) and 20 days (D20) following right middle cerebral artery ligation. At each testing time, the muscle length, width, and estimated volume of the isolated soleus muscle were recorded, subsequently followed by in-vivo muscle tension and sarcomere length measurement. The mass of the soleus muscle was measured at the end of testing to calculate muscle density. Two-way ANOVA with repeated measures was used to examine the differences in each of the dependent variable among the 3 time-point groups and between the 2 legs. The passive muscle stress of the impaired limbs in the D3 group (27.65 ± 8.37 kPa) was significantly lower than the less involved limbs (42.03 ± 18.61 kPa; P = 0.05) and the impaired limbs of the D10 (48.92 ± 14.73; P = 0.03) and D20 (53.28 ± 20.54 kPa; P = 0.01) groups. The soleus muscle density of the impaired limbs in the D3 group (0.69 ± 0.12 g/cm3) was significantly lower than the less involved limbs (0.80 ± 0.09 g/cm3; P = 0.04) and the impaired limbs of the D10 (0.87 ± 0.12 g/cm3; P = 0.02) and D20 (1.00 ± 0.14 g/cm3; P < 0.01) groups. The D3 group had a shorter sarcomere length (2.55 ± 0.26 µm) than the D10 (2.83 ± 0.20 µm; P = 0.03) and D20 group (2.81 ± 0.15 µm; P = 0.04). These results suggest that, while ischemic stroke may cause considerable changes in muscle tension and stress, sarcomere additions under increased mechanical loadings may be absent or disrupted post-stroke, which may contribute to muscle spasticity and/or joint contracture commonly observed in patients following stroke.